Strategic Inventory Control in Hospital Pharmacies: An ABC-VED Approach in a Hospital of Developing Country, Nepal - Prachhai, Deepak Bahadur; Dawadi, Sujan; Kharel, Sagun; Lamichhane, Binita; Shakya, Anoma; Dhakal, Prabesh; Bhandari, Keshav Raj; Pandey, Bipindra (International Journal of Silkroad Institute of Research and Training, 2025)
Background: Drug inventories management is crucial for maximizing resource use and minimizing hospital pharmacy related expenses. Method: This research sought to evaluate the medication inventory at hospital pharmacies with 50 beded capacity using the Always Better Control (ABC), Vital, Essential and Desirable (VED), and ABC-VED matrix analyses for the April 1, 2023, to March 30, 2024. The pharmacy maintained a stock of 1672 distinct medications, with a total yearly expenditure of NPR. 38,177,997.92/-. Result: According to the ABC analysis, drugs were divided into three groups based on their annual consumption value: Category A comprised 304 drugs (18.18%), accounting for 71.5% of the costs; Category B included 443 drugs (26.49%), consuming 19.48%; and Category C consisted of 925 drugs (55.32%), utilizing 9.02%. As per the VED analysis, medications were categorized as vital (16%), essential (36%), or desirable (48%) according to their criticality. The ABC-VED matrix identified 30.20% of the drugs as Category I, necessitating strict control; 41.8% as Category II, requiring moderate control; and 28% as Category III, allowing for relaxed control. Conclusion: This study underscores the importance of prioritizing high-value and critical medications for effective inventory management. Employing ABC-VED matrix analysis can substantially enhance patient care, optimize financial resources, and avert drug shortages in hospital pharmacies, especially in developing nations such as Nepal.